Integration of Immature Granulocytes Quantification With the Version 2.0 UniCel DxH 800 in the HematoFlow Strategy. Issue 4 (23rd April 2016) - Pastoret, Cedric; Ly Sunnaram, Beatrice; Fest, Thierry; Roussel, Mikael
Abstract : Objectives: Our aim was to define whether the early granulocyte cell marker (EGC%_DxH) parameter might replace immature granulocytes counts obtained by HematoFlow (IG%_HF) and/or manual differential count (IG%_manual). Methods: We conducted a study over a 10-day period in February 2014 whereby 402 samples were analyzed for the IG flag. We correlated the EGC%_DxH vs IG%_HF and IG%_manual, identified any discrepant results and finally looked at the impact on our workflow by incorporation of the EGC% into our WBC differential algorithm. Results: On an initial training set, a receiver operating characteristic (ROC) curve analysis showed a threshold of 0.9% for EGC%_DxH (sensitivity of 91.7%, specificity of 93.5% and an area under the curve of 0.965). Further analysis of the dataset (259 samples) found a correlation of the EGC%_DxH to all our IG% counting methods ( r  = 0.963). Incorporation of the EGC%_DxH into the WBC HematoFlow differential resulted in a 36% reduction of samples requiring HematoFlow and/or slide review. Conclusions: The EGC% generated by the DxH 800 can be easily incorporated into existing HematoFlow and slide review algorithms.